Evaluacion de clones de yuca con participacion de agricultores (Instrucciones) - Hernández Romero, Luis Alfredo (International Center for Tropical Agriculture, 1990)
A complementary methodology to select cassava clones in advanced stages of assessment is presented; this methodology should be carried out jointly by farmers and researchers and thus increase the possibility of adoption of the selected clones. An attempt was made to establish feedback between transferrer, researcher, farmer, and plant breeder, enabling the identification of selection criteria that should be incorporated into plant breeding programs. The procedure used to collect information is detailed as follows: information on the diagnostic process, selection of farmers, explanation of the survey (purposes, benefits and risks, responsibilities, role of the farmer), selection of clones, location of the trial on the selected farms, plot delimitation, evaluations (beginning, middle, and end of cropping cycle) and culinary quality tests, information recording (field book), monitoring of selected clones, and information analysis. (CIAT)